Host sweet preference modulates the salivary microbiome and its divergent associations with plaque-associated and non-plaque-related oral diseases - Li, Zhenzhen; Peng, Xiao; Wang, Qi; Guo, Liangying; Liu, Shanshan; Xu, Li (Frontiers in Microbiology, 2025)
BackgroundMicroorganisms play a critical role in the progression of oral diseases. However, it remains unclear whether the frequency of sweet consumption influences the salivary microbiota in both plaque-associated and non-plaque-related oral diseases.MethodsBased on salivary microbiome analysis, unstimulated saliva samples were collected from university students aged 17–20, including healthy controls (HC), dental caries (DC), and dental fluorosis (DF) groups, under different sweet consumption frequencies. Microbiota potentially critical in disease development were identified.ResultsNo significant differences in α- and β-diversity were observed among the three groups. However, distinct microbial structures at the genus and species levels were evident under different sweet consumption conditions. Under high sweet consumption, the caries group exhibited enrichment of microbiota closely associated with sugar metabolism and acid production (e.g., Streptococcus, Rothia), while Ralstonia was significantly enriched in the caries group, suggesting its potential role in high-sweet-induced caries development. Under low sweet consumption, the healthy control group showed enrichment of taxa such as Stenotrophomonas, potentially linked to ecological stability, whereas the dental fluorosis group demonstrated significant enrichment of Fastidiosipila, reflecting specific fluoride-induced selective pressure on the microbiome. This study indicates that although sweet consumption frequency did not significantly alter overall microbial diversity, it reshaped the oral microbiota structure in a disease-specific context. The caries group was more prone to developing a cariogenic microbial profile under high-sugar conditions, while the fluorosis group exhibited unique ecological adaptive characteristics.